Exchange Rate Pass-Through in Vietnam under the Impact of Inflationary Environment - Tran, Ngoc Tho (University of Economics Ho Chi Minh City, 2023)
This article addresses the exchange rate pass-through to domestic prices under the impact of inflation. Using TVAR based approach and the variables of inflation, nominal effective exchange rate (NEER), output gap, and interbank rate in addition to monthly data applied to the period of 2000M1–2014M12, we find a non-linear relation in the pass-through to inflation along with the two thresholds of its. Being above or below the thresholds results in different levels of the exchange rate pass-through, which is consistent with previous findings, with unclear/clear evidence found below/above the threshold of 0.3395%/month respectively. In the case of positive shocks of the exchange rate, the inflation is suggested to enormously rise and then return to equilibrium. We also attempt to clarify several distinct features of Vietnam affecting the pass-through and draw a few implications.